Coccydynia and Disability on Postpartum Vaginal Delivery Women - Vishnu, Priya; Jagatheesan, Alagesan; Dasarapu, Indrani (INTI International University, 2022)
Background and Objective: Coccydynia is strain or discomfort in the area of coccyx. The common causes are trauma in the gluteal region, repetitive microtrauma, or childbirth. Delivery through vagina is often related to damage of sacrococcygeal ligaments and progress of the fetus through the birth canal may cause acute damage to the coccyx, this can be further provoked by forceps delivery. Although tension and damage of ligaments attached to coccyx have been thought to be the general cause for coccydynia occurring after childbirth. A study was conducted in France on postpartum women with coccydynia have concluded that 7.3% of cases of coccydynia in female related after delivery. Hence, this study was taken with an intention to find the coccydynia and disability on vaginal delivery postpartum women. Method: An observational study was conducted on 378 vaginal delivery postpartum women in Saveetha Medical College and Hospital, Chennai. This study was done by using Oswestry Questionnaire for disability and examination for coccydynia between the age of 20 and 40 years of postpartum vaginal delivery women. Results: Among 378 postpartum women 196 have coccydynia with age from 20 to 40 years. The postpartum women according to Oswestry Scoring 96 women were in moderate disability, 69 women were in severe disability and 31 women were crippled. Conclusion: From the results it was concluded that coccydynia and disability on postpartum vaginal delivery women was 51 percent.